Anti-biofilm efficacy of green-synthesized ZnO nanoparticles on oral biofilm: In vitro and in silico study - Lahiri, Dibyajit; Ray, Rina Rani; Sarkar, Tanmay; Upadhye, Vijay Jagdish; Ghosh, Sujay; Pandit, Soumya; Pati, Siddhartha; Edinur, Hisham Atan; Abdul Kari, Zulhisyam; Nag, Moupriya; Ahmad Mohd Zain, Muhammad Rajaei (Frontiers in Microbiology, 2022)
The development of biofilm on the biotic and abiotic surfaces is the greatest challenge for health care sectors. At present times, oral infection is a common concern among people with an unhealthy lifestyle and most of these biofilms-associated infections are resistant to antibiotics. This has increased a search for the development of alternate therapeutics for eradicating biofilm-associated infection. Nanobiotechnology being an effective way to combat such oral infections may encourage the use of herbal compounds, such as bio-reducing and capping agents. Green-synthesis of ZnO nanoparticles (ZnO NP) by the use of the floral extract of Clitoria ternatea, a traditionally used medicinal plant, showed stability for a longer period of time. The NPs as depicted by the TEM image with a size of 10 nm showed excitation spectra at 360 nm and were found to remain stable for a considerable period of time. It was observed that the NPs were effective in the eradication of the oral biofilm formed by the major tooth attacking bacterial strains namely Porphyromonsas gingivalis and Alcaligenes faecalis, by bringing a considerable reduction in the extracellular polymeric substances (EPS). It was observed that the viability of the Porphyromonsas gingivalis and Alcaligenes faecalis was reduced by NP treatment to 87.89 ± 0.25% in comparison to that of amoxicillin. The results went in agreement with the findings of modeling performed by the use of response surface methodology (RSM) and artificial neural network (ANN). The microscopic studies and FT-IR analysis revealed that there was a considerable reduction in the biofilm after NP treatment. The in silico studies further confirmed that the ZnO NPs showed considerable interactions with the biofilm-forming proteins. Hence, this study showed that ZnO NPs derived from Clitoria ternatea can be used as an effective alternative therapeutic for the treatment of biofilm associated oral infection.